Perceptions of Occupational Therapy Involvement in School Mental Health: A Pilot Study - Susan M. Cahill; Brad E. Egan (Scholarworks @ WMU, 2017)
Background: Mental health providers outside of occupational therapy, including those who work in school systems practice, often do not fully understand the contribution that occupational therapy practitioners can make to the delivery of mental health services. Method: The purpose of this mixed methods pilot study is to describe how instructional support staff from one special education cooperative learned about occupational therapy's role in school mental health and to explain how this education changed the instructional support staff members' perceptions regarding the involvement of occupational therapy practitioners in school-based mental health services. Results: Instructional support staff's perceptions about occupational therapy changed as a result of the training. Discussion: Occupational therapy practitioners can be viewed as valuable members of the school mental health team if other practitioners are educated about their scope of practice.